Collective impact facilitators 2019 review for LP170100480 ARC linkage project creating pathways to child wellbeing in disadvantaged communities (2019-2020) - Branch, Sara (Griffith University, 2021)
A central feature of the CREATE-ing Child Wellbeing research initiative is the development of a Prevention Translation and Support System (PTSS) in order to support evidence-based collaborative preventive action. This included the development of human and electronic resources that are responsive to the needs of children, families, community service deliverers, and schools. The Collective Impact Facilitator role constitutes a central element of the human resources within the PTSS. In addition to Collective Impact Facilitators (CIFs), we often call people who perform this role Collective Change Facilitators. CIFs are ‘system intermediaries’ who act as a bridge between researchers in the support system and the consumers, deliverers, and designers of services. This review study sought to understand the role of CIFs within CfC during the second phase of the research initiative (2016-2019). In this period a new model of the CIF role was implemented. In contrast to Phase 1 (2014-2016) when CIFs were recruited and supervised by Griffith University, in Phases 2 and 3 they were recruited and supervised by one of the CREATE initiative’s NGO partner organisations.